The Effect of Profitability Towards Financial Distress - Thomson Sitompul; Joventy Lim; Jessica Jolie Wong (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study investigates the effect of profitability on financial distress in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2023, using a unique dataset from that period. From a population of 226 companies, 46 were selected through purposive sampling, resulting in 322 observation units. The analysis was conducted using multiple linear regression in SPSS. This research involves one dependent variable, one main independent variable, and four control variables. Financial distress, the dependent variable, is measured using the Altman Z-Score model. Profitability, the main independent variable, is calculated using return on assets (ROA). The control variables include leverage (measured by debt to asset ratio/DAR), liquidity (current ratio/CR), activity (assets turnover), and firm size (natural logarithm of total assets). The findings indicate that profitability and activity have a significant positive effect on financial distress, while leverage shows a significant negative effect. Liquidity and firm size do not have a significant impact on financial distress.